Developmental Psychology of Learners: Adult Religious Development, Influencing Factors, and Developmental Dynamics - Muhammad Abu Ramdani; Eva Latipah; Rizqi Nur Abdillah; Habibah Khansa Fatimah; Muchlisatun Nisa (Linguanusa : Social Humanities, Education and Linguistic, 2025)
Introduction to The Problem: The evolution of religious development in adults constitutes a pivotal aspect within the academic study of religious education and the psychology of religion. With advancing age, an individual’s comprehension and disposition towards religion may undergo transformations, mediated by lived experiences, the socio-environmental context, and processes of personal introspection. Purpose: The objective of this research is to theoretically examine the process of religious development/maturation in adulthood and to identify the contributing factors that influence this trajectory. This study holds significance as it aims to provide a conceptual framework for religious education initiatives that are more attuned to the spiritual needs of the adult population. Design/methods/approach: This study employed a library research methodology (literature review), involving the systematic collection and analysis of diverse scholarly sources, including books, academic journals, articles, and previous research findings pertaining to adult religious development. This approach enabled the researcher to achieve a deeper understanding of existing concepts and established theoretical frameworks. Findings: The findings of the review indicate that religious development in adulthood is not a static process, but rather a dynamic trajectory that is subject to situational variability. Adults typically begin to engage in a deeper exploration of religious meaning, shifting from a form of religiosity based solely on adherence to established rules toward a more personal orientation aligned with their individual lived experiences. Furthermore, they tend to become more openminded, demonstrate greater judiciousness in navigating religious differences, and exhibit a heightened concern for ethical values. Nonetheless, this developmental process is heterogeneous, contingent upon each individual’s educational background, cultural context, and idiosyncratic life experiences. Research implications/limitations: A principal limitation of this research is the absence of primary empirical data collection, as the findings are derived exclusively from theoretical frameworks and published literature. Originality/value: Notwithstanding this constraint, the study remains valuable by enhancing the current understanding of how religiousness evolves in adulthood, thus providing a crucial theoretical foundation for subsequent, more empirical research endeavors.